Front Cover: Transmembrane Transport of Bicarbonate Unravelled (Chem. Eur. J. 26/2021). Issue 26 (28th April 2021) - Martínez‐Crespo, Luis; Hewitt, Sarah H.; De Simone, Nicola Alessandro; Šindelář, Vladimír; Davis, Anthony P.; Butler, Stephen; Valkenier, Hennie
Abstract : The development of synthetic bicarbonate transporters is of high interest for potential therapeutic applications. This work presents a new assay to study bicarbonate transport, based on a europium complex that is encapsulated inside liposomes and reports changes in the intravesicular concentration of bicarbonate in a direct and highly sensitive way. The assay revealed that transporters can act via different mechanisms, involving actual transport of HCO3 − anions or passive diffusion of CO2 . More information can be found in the Full Paper by S. Butler, H. Valkenier, et al. (DOI: 10.1002/chem.202100491 ).